The danger of chemical weapons in Syria: Unfinished disarmament and international control efforts - Oliver Meier (Stiftung Wissenschaft und Politik (SWP), 2016)
On 4 January 2016, the Organisation for the Prohibition of Chemical Weapons (OPCW) in The Hague announced that the process of destroying Syrian chemical weapons had been completed. Despite that declaration of success, problems obviously persist. Since April 2014, the civil war parties have accused each other in more than one hundred cases of having used chemical weapons. In more than twenty incidents the OPCW has confirmed the use of chemical weapons. The United States also accuses Syria of having kept part of its chemical arsenal. The international community has established three institutional mechanisms to shed light on chemical weapons-related issues. Clarification of key questions - whether Syria still possesses a chemical weapons potential, where chemical weapons have been used and who is responsible for their use - under conditions of war will be a challenge. Despite the poor prospects of success, the investigations are important to reduce the risks of further chemical weapons use. Independent of the state of the peace process, international control efforts should be pursued persistently and with a long-term view. Wherever possible, new control capabilities developed in the context of Syrian crisis should be consolidated. (SWP Comments)
Keywords: 320